2016
DOI: 10.1021/acssensors.6b00452
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Detection of Hypoxia Using a Ratiometric Quantum Dot-Based Oxygen Sensor

Abstract: A quantum-dot based ratiometric fluorescent oxygen probe for the detection of hypoxia in live cells is reported. The system is comprised of a water-soluble near-infrared emissive quantum dot conjugated to perylene dye. The response to the oxygen concentration is investigated using enzymatic oxygen scavenging in water, while in vitro studies were performed with HeLa cells incubated under varying O2 levels. In both cases a significant enhancement in dye/QD emission intensity ratio was observed in the deoxygenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The emission lifetimes of the nanoprobe also reduced from 4031 ns to 836 ns at O 2 concentrations of 0% to 21%, respectively. In vitro tests confirmed that this probe was capable of intracellular hypoxia imaging in HeLa cells [66]. …”
Section: Nanoparticle Based Probesmentioning
confidence: 97%
See 1 more Smart Citation
“…The emission lifetimes of the nanoprobe also reduced from 4031 ns to 836 ns at O 2 concentrations of 0% to 21%, respectively. In vitro tests confirmed that this probe was capable of intracellular hypoxia imaging in HeLa cells [66]. …”
Section: Nanoparticle Based Probesmentioning
confidence: 97%
“…(Figure reproduced from reference [66]; use permitted under the Creative Commons Attribution License CC BY 4.0. )…”
Section: Figurementioning
confidence: 99%
“…Currently, these frequently-used self-referenced luminous nanoparticles mainly consist of dye-embedded silica, 153, 154 gold nanoclusters (AuNCs), 155157 fluorescent bovine serum albumin nanoparticles, 158 Cdots, 159, 160 , silicon nanodots, 161 or quantum dots (QDs). 162, 163 Through a combination of the corresponding target-sensitive fluorescent dye units with unique responses to target analytes or molecular events, these dual-emission nanoparticle-dye nanoconjugates have been extensively applied for ratiometric sensing and imaging of diverse physical and physiological changes. For example, Tian et al applied Cdots as a reference unit and hydroethidine (HE) as a specific response unit to develop a dual emission nanoparticle-dye nanocomplex for ratiometric sensing and imaging of superoxide anion changes upon oxidative stress in cancer cells.…”
Section: Ratiometric Fluorescence Nanoprobesmentioning
confidence: 99%
“…Photoelectrochemical sensors using TQDs are based on change in photocurrent due to chemical changes by enzymes, QD-protein interactions and binding reactions between biomolecules [47]. Reported applications include photoelectrochemical detection of acetylcholine [48], oxygen [49], epinephrine [50], and hydrogen [51], [52] to name a few. Although the use of TQDs in a range of biosensing and bioimaging applications has been explored, their cytotoxicity has been a cause of concern.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%